Ubuntu Linux Bible - Clinton, David; Negus, Christopher (Bible, 2020)
Ubuntu Linux Bible (version 19.10) addresses the information needed for the complete spectrum of Ubuntu users, from desktop users to server administrators, including those new to Linux who may be setting up Linux servers for the first time. The book provides complete information presented in such a way that new users have all of the information that they need, while experienced Linux users can skip directly to the details that they require. Covering the recently released 19.10, as well as the previous version, this book will cover Getting Started with Ubuntu, Ubuntu for Desktop Users, and Ubuntu for System Administrators This book is organized into four parts: "Getting Started with Ubuntu Linux," "Ubuntu for Desktop Users," Ubuntu for System Administrators," and "Configuring Servers on Ubuntu." Making the most of the wide variety of software that is included with Ubuntu Linux. The "Desktop Users' section of the book is task-oriented, explaining how to do user-oriented tasks like read email, surf the web, create and publish documents, work with spreadsheets, create presentations, play games, create and edit graphics, and work with common consumer IoT electronic devices. Managing Ubuntu systems, explaining fundamental Linux system administration topics such as creating and managing users, backing up the system, adding new printers and disks to the system, network configuration, and using Ubuntu wirelessesly. Using Ubuntu to support network servers. Ubuntu is primarily targeted for desktop users but can also be used in an enterprise environment to provide core network services, where it is especially attractive due to its support for a huge number of languages. This part contains chapters explaining how to set up servers for the Web, electronic mail, print services, networked file sharing, DHCP (network address management), and DNS (network name/address resolution).